Ionic Conductivity Studies on Nano ZnO Incorporated PVC-PEG Blend Based Polymer Composite Electrolytes - Ravindran1, D.; Vickraman2, P. (Asian Journal of Chemistry, 2013)
Nano-sized ZnO was prepared by sol-gel method and it was incorporated as filler in PVC-PEG blend based solid polymer electrolytes with lithium perchlorate as salt. The (PVC:ZnO) ratio was systematically varied in order to study its effect on the ionic conductivity behaviour of electrolyte membranes. The membranes were subjected to XRD and AC impedance analysis. The analysis shows that the conductivity profile was strongly influenced by the (PVC:ZnO) ratio. The conductivity profile exhibits two maxima one occurring at 0.5 wt % and the other at 4 wt % of filler. The membrane with composition, (PVC:ZnO):PEG:PC:LiClO4 = (21:4):15:50:10 exhibits higher conductivity of 6.052 × 10-6 S/cm at room temperature and this value is 10 times higher than that of filler free electrolytes.